Three new species and one new record of the leafhopper genus Agnesiella Dworakowska, 1970 (Hemiptera: Cicadellidae: Typhlocybinae: Typhlocybini) from China - Yan, Bin; Yang, Mao-Fa (Zootaxa, 2016)
Three new species and one species newly recorded from China in the genus Agnesiella Dworakowska, 1970 are described and illustrated: A. (Draberiella) xantha sp. nov., A. (Draberiella) erosa sp. nov. and A. (Draberiella) latusa sp. nov., A. (Draberiella) azra Dworakowska, 1994 new record. A key to known Chinese species is given. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).